The Global pound conference in Singapore: A conversation on the future of dispute resolution - Dorcas QUEK ANDERSON (Institutional Knowledge at Singapore Management University, 2016)
The inaugural conference of the Global Pound Conference Series was hosted by Singapore in March 2016. A key feature of the series was the gathering of views from a wide range of stakeholders concerning the current development of dispute resolution, identifiable gaps and ways to enhance access to justice in the future. This article analyses preliminary trends emerging from the views elicited at the conference, offering views on the current state of Singapore’s dispute resolution landscape; the future directions of dispute resolution; the future practice modality of legal advisors; and ways to engender change in dispute resolution and access to justice.